Analisis Pengaruh Struktur Modal Terhadap Profitabilitas Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia: Pengabdian - Kasmaini; Rina Malahayati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
A company's success is often judged by its reported profitability. If a company wants to survive, it must maintain profitability by reflecting strong performance. The better a company's performance, the higher its profitability, which can attract investors. In order for a company to easily obtain capital from outside or attract investors to invest their capital, the company must have profitability or profit, where the ultimate goal of the company is to obtain maximum profit or profit (. Another thing that can affect the profitability of a company is the capital structure. It can be believed that the capital structure can affect the profitability of the company and the rate of growth of a company. The decision regarding capital structure, namely how the company finances its assets through a combination of debt and equity, is one of the crucial financial decisions. In facing an increasingly competitive environment, decisions regarding capital structure are very important for every side of the business organization. One of the important decisions faced by financial managers in relation to the company's operational activities is the funding decision. The optimal capital structure is one of the considerations between using own capital and using long-term loans. Increasing the capital structure owned by the company will return optimally to the company that makes a profit and also shareholders. In this case, the capital structure is important in increasing the company's profitability and the company's sustainability.